Challenging Global Capitalism - Pizzolato, N. author. aut Link
XIV, 252 p.
Keywords: In the 1950s, 1960s, and 1970s, Detroit and Turin were both sites of significant political and social upheaval. This comparative and transnational study examines the political and theoretical developments that emerged in these two "motor cities" among activist workers and political militants during these decades.